Advances and challenges in pretreatment technologies for bioethanol production: A comprehensive review - Sanyam Jain; Shushil Kumar (Sustainable Chemistry for Climate Action)
Bioethanol production from biomass is a promising avenue for sustainable energy, yet the high cost of pretreatment processes poses significant economic challenges. This paper explores the critical role of pretreatment in enhancing bioethanol yield and reducing production costs. Various pretreatment methods, including physical, chemical, physicochemical, and biological techniques, are reviewed and further analyzed for their effectiveness in breaking down lignocellulosic biomass into fermentable sugars. Emphasis is placed on recent technological advancements and innovations that improve efficiency and cost-effectiveness. The paper reviews the latest research on combined pretreatment approaches that have shown potential in overcoming recalcitrance and increasing sugar yield. Also, the role of nanotechnology in biomass pretreatment has been discussed. The economic implications of different pretreatment strategies are discussed, highlighting cost-benefit analyses and the potential for scalability. By addressing the complexities and advancements in pretreatment technologies, this study aims to provide a comprehensive understanding of the role of optimizing pretreatment processes in significantly enhancing hydrolysis efficiency. The findings underscore the importance of continued research and development to achieve better economic viability and environmental sustainability in bioethanol production.